Pendampingan Manajemen Usaha Tani Jagung Berbasis Good Agriculture Practices di Koya Barat, Kota Jayapura - Agustinus Numberi; Isma Shalihi Ahlia; Fanny Kristin Tantyah Sitompul; Iriando Wijaya; Musa Kris Payokwa (Universitas Muhammadiyah Semarang, 2026)
Low financial administrative literacy stands as a primary determinant impeding the acceleration of Good Agricultural Practices (GAP) standards adoption within smallholder farming structures. This community service program aims to improve the management skills of the Setia Tani Farmer Group in Koya Barat, Jayapura City, through the provision of a practical bookkeeping cash instrument. The implementation methodology integrated andragogical approaches and participatory training operationalized across five distinct phases, synergized organically with Local Agricultural Extension Officers (PPL). Evaluation metrics indicated an absolute transformation in partners' cognitive capacity, validated by a leap in comprehension scores from 76% to 100% in the post-test. Within the psychomotor dimension, the partners' mechanistic skills in classifying capital components, recording cash flows, and accurately calculating final balances achieved a score range of 4 to 5 (good to very good category). The managerial impact is reflected in the institutionalization of financial accountability that reduces operational cost inefficiencies, whereas the social impact is demonstrated by the strengthening of institutional social capital and collective readiness to meet the traceability requirements for GAP certification.